2017
DOI: 10.24843/ejmunud.2018.v7.i02.p15
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Stres Kerja Dan Kepuasan Kerja Terhadap Komitmen Organisasi Karyawan Pbf. Pt. Banyumas Denpasar

Abstract: Organizational commitment is the involvement of individuals, feelings of belonging and loyalty to the company or feel to be part of the organization to achieve organizational goals. In order for employees to have high organizational commitment, an organization needs to pay attention to the factors that influence organizational commitment such as personal factors, organizational factors and Non-organizational factors. The purpose of this study is to determine the effect of job stress and job satisfaction on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
2
6
0
9
Order By: Relevance
“…This shows that high work stress will reduce organizational commitment. In line with the research of Noor et al, (2016), Ariawan & Sriathi (2017) and Ekienabor (2019), it shows that job stress has a negative and significant effect on organizational commitment. This means that if the company can reduce and manage the level of stress experienced by employees, it will increase the organizational commitment of employees to the company.…”
Section: The Effect Of Job Stress and Organizational Commitmentsupporting
confidence: 89%
“…This shows that high work stress will reduce organizational commitment. In line with the research of Noor et al, (2016), Ariawan & Sriathi (2017) and Ekienabor (2019), it shows that job stress has a negative and significant effect on organizational commitment. This means that if the company can reduce and manage the level of stress experienced by employees, it will increase the organizational commitment of employees to the company.…”
Section: The Effect Of Job Stress and Organizational Commitmentsupporting
confidence: 89%
“…According to Karambut (2012) unresolved job stress can lead to a decrease in employee organizational commitment and his research found that job stress negatively affects organizational commitment. The same thing was stated by Ariawan & Sriathi (2017), Iresa et al (2015), Puspa et al (2014), Putri & Martono (2015), Wibowo et al (2015), Widayanti & Sariyathi (2016) who found the results that job stress had a negative effect on employee intentions to stay with the organization or organizational commitment.…”
Section: Introductionsupporting
confidence: 64%
“…Although stress has a value that is negative but the stress does not affect the commitment of the organization. Different results were expressed by Widayanti & Sariyathi (2016) and Ariawan & Sriathi (2017) which stated that job stress had a significant negative effect on organizational commitment. According to Hakim & Hidayat (2018), organizational commitment is often associated with compensation policies, according to him, higher compensation will increase organizational commitment.…”
Section: The Effect Of Job Stress On Organizational Commitmentmentioning
confidence: 91%
“…Dwiki & Riana (2018) mengatakan bahwa kepuasan kerja berpengaruh positif signifikan terhadap komitmen organisasi. Ariawan & Sriathi (2018) mengatakan bahwa kepuasan kerja berpengaruh positif dan signifikan terhadap komitmen organisasional. Rumangkit.…”
Section: No Pernyataan Sts Ts Cs S Ssunclassified